The Effect of Marketing Capability and Financial Capability on Improving Coffee Commodity Performance and Implications for Value Added in Kerinci Regency - Syofya, Heppi Heppi; Syofya, Heppi (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
This research study investigates the effect of marketing capability and financial capability on improving coffee commodity performance and its implications for value added in Kerinci Regency. A quantitative research approach was used, and data were collected from 110 coffee industries through a structured survey. Data were analyzed using Smart-PLS 4 software, using confirmatory factor analysis and path analysis. The results showed significant positive relationships between marketing capability and coffee commodity performance, financial capability and coffee commodity performance, marketing capability and value-added, and financial capability and value-added. The findings highlight the importance of marketing capabilities and financial capabilities in improving coffee commodity performance and generating added value. This study provides practical implications for coffee industry stakeholders and suggests strategies to strengthen marketing and financial capabilities to improve performance and value creation in the coffee industry. However, it is important to consider the limitations of this study, such as the specific geographical context and reliance on self-reported data. Future research could replicate this study across different regions and use a mixed-methods approach to gain a more comprehensive understanding